Efficient Fabrication and Assessment of Telmisartan Fast-Dissolving Films Using Solvent Casting Approach - Mishra, Ashish Sriram; Dutta, Gouranga; Sugumaran, Abimanyu (Indian Journal of Pharmaceutical Education and Research, 2025)
Introduction: Telmisartan (TLM) is a common angiotensin II receptor antagonist used to treat hypertension. However, the drug's limited bioavailability and delayed onset duration diminish its efficacy. To address these concerns, fast-dissolving TLM films were fabricated in this investigation using the solvent-casting method. Objectives: This investigation aimed to create a film formulation of TLM, a widely prescribed antihypertensive medication. The objectives were to optimize the formulation parameters and assess the physicochemical properties, drug release profile and dissolution behavior of the rapidly dissolving TLM film. Materials and Methods: The solvent casting method efficiently produces homogeneous, flexible films with desirable properties, such as high drug dosage and rapid dissolution. The Box-Behnken design was utilized to investigate the effect of three distinct, independent variables on the physicochemical properties of FDFs to determine the optimal conditions for FDF production. The films' physicochemical properties, drug release characteristics and pharmacokinetic parameters were evaluated. Results and Discussion: The results demonstrated that the films had superior dissolution properties and improved bioavailability compared to conventional TLM tablets, suggesting their potential use as a TLM delivery system. Conclusion: The rapidly dissolving film comprising TLM, which exhibits promising drug release
Keywords: Fast dissolving film; Solvent casting Method; Pectin; PVP; TLM